Ammonia control and neurocognitive outcome among urea cycle disorder patients treated with glycerol phenylbutyrate1. Issue 6 (3rd January 2013) - Diaz, George A.; Krivitzky, Lauren S.; Mokhtarani, Masoud; Rhead, William; Bartley, James; Feigenbaum, Annette; Longo, Nicola; Berquist, William; Berry, Susan A.; Gallagher, Renata; Lichter‐Konecki, Uta; Bartholomew, Dennis; et al.
Abstract Glycerol phenylbutyrate is under development for treatment of urea cycle disorders (UCDs), rare inherited metabolic disorders manifested by hyperammonemia and neurological impairment. We report the results of a pivotal Phase 3, randomized, double‐blind, crossover trial comparing ammonia control, assessed as 24‐hour area under the curve (NH3‐AUC0‐24hr), and pharmacokinetics during treatment with glycerol phenylbutyrate versus sodium phenylbutyrate (NaPBA) in adult UCD patients and the combined results of four studies involving short‐ and long‐term glycerol phenylbutyrate treatment of UCD patients ages 6 and above. Glycerol phenylbutyrate was noninferior to NaPBA with respect to ammonia control in the pivotal study, with mean (standard deviation, SD) NH3‐AUC0‐24hr of 866 (661) versus 977 (865) μmol·h/L for glycerol phenylbutyrate and NaPBA, respectively. Among 65 adult and pediatric patients completing three similarly designed short‐term comparisons of glycerol phenylbutyrate versus NaPBA, NH3‐AUC0‐24hr was directionally lower on glycerol phenylbutyrate in each study, similar among all subgroups, and significantly lower (P < 0.05) in the pooled analysis, as was plasma glutamine. The 24‐hour ammonia profiles were consistent with the slow‐release behavior of glycerol phenylbutyrate and better overnight ammonia control. During 12 months of open‐label glycerol phenylbutyrate treatment, average ammonia was normal in adult and pediatric patients and executive function among pediatric patients, including behavioral regulation, goal setting, planning, and self‐monitoring, was significantly improved. Conclusion: Glycerol phenylbutyrate exhibits favorable pharmacokinetics and ammonia control relative to NaPBA in UCD patients, and long‐term glycerol phenylbutyrate treatment in pediatric UCD patients was associated with improved executive function (ClinicalTrials.gov NCT00551200, NCT00947544, NCT00992459, NCT00947297). (HEPATOLOGY 2012)